Spatial distribution and migration of lead and zinc and the influence of parent materials in typical paddy soils of Hunan Province, China - Xiang, Yi-fan; Wan, Da-juan; Wang, Chen-ran; Huang, Jun-lin; Cao, Xue-ying; Chen, Jia-qi; Ouyang, Ning-xiang (Environmental monitoring and assessment, 2023)
This study aimed to investigate the distribution and migration characteristics of lead (Pb) and zinc (Zn) in paddy soils in Hunan Province, China. A total of 343 soil samples from 63 profiles were collected from typical regions. The concentration, spatial distribution, and migration behaviors of Pb and Zn in the paddy soils were examined. The results showed that (1) the concentration ranges of Pb and Zn in the surface layer were 17.62–114.07 mg/kg and 44.98–146.84 mg/kg, respectively. (2) The content was higher in the middle and lower reaches of the Xiangjiang River basin horizontally and exhibited shallow enrichment characteristics vertically. (3) Pb migration was weaker than Zn migration, and the parent material had the most significant influence on Pb and Zn content in the bottom soil layer. The research results will clarify the characteristics of Pb and Zn contents in paddy soils in Hunan Province, further understand the horizontal distribution and vertical migration and transformation characteristics of Pb and Zn contents in paddy soils, and provide basic data for scientific rice cultivation and safe food production.